Learning and teaching the water method (with videos) - Friedland, Shai (Landes Bioscience, 2011)
The water method is an insertion technique for colonoscopy which has recently become popular owing to its demonstrated ability to decrease patient pain and sedation requirements. This review focuses on learning and teaching the water method. Data from the United States and Asia suggests that trainees at all levels of experience can safely learn and utilize the water method. Demonstrated benefits in some of the reviewed studies include lessened sedation requirements, less pain for patients and increased cecal intubation rates in minimally sedated patients. These benefits are realized without compromising safety, adenoma detection rates, or procedure times.